Ecological risk assessment of marine resources caught as bycatch in industrial bottom trawl shrimp fishery in the Amazon Continental Shelf - Peixoto, Ualerson I.; Sporcic, Miriana; Hobday, Alistair J.; Bentes, Bianca; Passarone, Rafaela; Fredou, Flavia Lucena; Isaac, Victoria Judith (Frontiers in Marine Science, 2025)
Ecological risk assessment (ERA) has been widely used to assess species’ vulnerability to the impacts of fishing and then to prioritize any additional management actions to reduce impacts. The Ecological Risk Assessment for the Effects of the Fishing framework is based on a hierarchy of qualitative and semi-quantitative tools that work well in data-deficient situations. This study first used the Scale Intensity and Consequence (SICA) and Productive and Susceptibility Analyses (PSA) tools to evaluate the impacts of the industrial bottom trawl of southern brown shrimp on the Amazon Continental shelf in Northern Brazil. A total of 540 species were identified as having direct or indirect interaction with the trawls. The SICA identified that the main risk was related to fishing capture activities, potentially impacting the species’ population size. Of the 47 species evaluated in the PSA, 12 displayed low vulnerability, 23 displayed moderate vulnerability, and 12 displayed high vulnerability to the impacts of fishing. Future fisheries management should focus on reducing species vulnerability by prioritizing data collection for the most at-risk species. Also, fishing gear modification, such as bycatch exclusion devices (BRDs), should be employed to decrease the species’ vulnerability.